Saffron’s Effect on Blood Glucose Control in People with Type 2 Diabetes Mellitus - Dewi Siti Oktavianti; Irfan Said; Alfonsa Reni Oktavia; Rani Rahmasari Tanuwijaya (Indonesian Contemporary Nursing Journal, 2022)
Introduction: Diabetes mellitus is a chronic disease that increase blood glucose owing to the body’s inability to make or use insulin properly. Chronic hyperglycemia is a significant issue for those with diabetes mellitus since it can result in a variety of problems. Controlling blood sugar is one of the therapies to prevent, inhibit and decrease diabetes-related problems. Consuming Saffron is a non-pharmacological way to enhance blood glucose management. Saffron include Crocins, Picrocrocin, and Safranal, all of which have hypoglycemic properties, improve insulin sensitivity, and help manage blood glucose. The purpose of this study is to assess the effect of Saffron (Crocus Sativus) on person with type 2 diabetes mellitus in terms of blood glucose control. Method: The research employed a quasi experimental approach, comprising a Pre-and post-test with control. Purposive sampling was used to split 54 respondents into two groups; 27 intervention groups and 27 control groups. The research was conducted in RW 09 Kelurahan Kebayoran Lama Utara in Jakarta Selatan. The paired T Test is applied for statistical analysis. Result: The results of this study indicated that Saffron had a substantial effect on blood glucose levels in patients with type 2 diabetes mellitus in the intervention group with a P-value 0,005 (P value < 0,05). Conclusion: Saffron can be used as a non-pharmacological treatment to help control blood glucose levels and avoid diabetic complications.